Study on cooperative emergency medical service system and mobile app development. (2017) - Xie, Pingjia; Tang, Yuliang; Xu, Le
Emergency medical treatment is an important component of public health, and its service quality is directly related to people's health and safety. But in the traditional emergency medical service mode, the relevant departments are relatively isolated and dispersive, which results in vital information cannot be shared in real-time. This study argues the application architecture and framework of a new cooperative emergency medical service system (CEMSS). The system enables effective information communication among emergency command centre (ECC), ambulances and the hospital dispatching centre, and makes doctors in the ambulances with experts of the hospital related departments work in synergy. The mobile app based on Android operating system is developed to promote convenience and flexibility. The proposed system can help doctors shorten the treatment time, improve the service quality and reduce the damage for patients.